One generalist or several specialist species? Wide host range and diverse manipulations of the hosts' web‐building behaviour in the true spider parasitoid Zatypota kauros (Hymenoptera: Ichneumonidae). Issue 6 (14th June 2018) - Korenko, Stanislav; Spasojevic, Tamara; Pekár, Stano; Walter, Gimme H.; Korenková, Vlasta; Hamouzová, Kateřina; Kolářová, Michaela; Kysilková, Kristýna; Klopfstein, Seraina
Abstract: Parasitoid wasps of the Polysphincta genus‐group are highly specialised on their spider hosts, and most of them are known to manipulate their hosts into building a special web in which the parasitoid pupates. Trophic niche and the plasticity of host use were investigated in the koinobiont parasitoid Zatypota kauros Gauld from Queensland, Australia. We found that Z. kauros attacks spider hosts from different families, each differing widely in their web‐building behaviours, which makes it unique in the breadth of its host range. Molecular analyses revealed that the taxon Z. kauros contains three divergent mitochondrial lineages. Lineage A was associated exclusively with spiders of the genus Anelosimus (Theridiidae), which builds tangle webs; lineage B was associated with the genus Cyrtophora (Araneidae), which weaves tent webs; and lineage C was associated with a broad range of hosts, including spiders of both the families Araneidae and Theridiidae. Unique host manipulations could be observed in the web‐building behaviours of the different host groups. Nevertheless, nuclear data from two ribosomal genes and three introns did not add any support to the existence of different evolutionary lineages, nor did they coincide with the different host groups. The partial correspondence of mitochondrial lineage and host use, together with an apparent mito‐nuclear conflict might indicate maternal effects or very recent and/or incomplete speciation in this taxon. Given their wide host range and intriguing interactions with their hosts, the Z. kauros complex represents a promising system for studying parasitoid specialisation and its potential impact on speciation.